PERTIMBANGAN HAKIM TERHADAP PERMOHONAN PRAPERADILAN DALAM PERKARA TINDAK PIDANA PENGGELAPAN PAJAK NOMOR 03/PID.PRA/2015/PN.PDG - Telaumbanua, Bezanolo; Fahmiron, Fahmiron (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
These days, objection with band of praperadilan have old tuff to Indonesia society. Along with existence of growth of is understanding of society will the truth of of law so that/ to be its rightss as free society and independence fufilled. If us pay attention that inseparable law of society, there is reason also to say that the source of law is society. Even if that way, still need furthermore clarification that such of society here is relation/link among/between individual in an coexistence. Source of law in fact is awareness of society whereof which is felt fair in arranging peaceful and orderly social life. As for problems which is told in this thesis is first, what becoming the reason of application in raising objection to doing an injustice embezzlement of Iease ? Both/ second, how onsideration of judge to application of raperadilan raised by doing an injustice embezzlement of Iease at District Court of Klas I A Field.